Hubungan Emotional Distress dengan Internet Gaming Disorder pada Mahasiswa - Leonora Mega Famella Sembiring; Lina Natalya; Nanik Nanik (Kuras Institute, 2026)
Generation Z demonstrates a high intensity of internet use and is particularly vulnerable to emotional distress, including anxiety and depression, due to academic and social demands. Online gaming is frequently used as a form of entertainment and a coping strategy; however, excessive gaming may develop into Internet Gaming Disorder (IGD). This study aimed to examine the association between emotional distress and Internet Gaming Disorder among university students who play Mobile Legends: Bang Bang. A quantitative cross-sectional survey was conducted with 262 university students in Surabaya selected through purposive sampling. Data were collected using the Internet Gaming Disorder Scale, the Generalized Anxiety Disorder-7 (GAD-7), and the Patient Health Questionnaire-9 (PHQ-9), and were analyzed using correlation and linear regression analyses. The results revealed that emotional distress was significantly associated with Internet Gaming Disorder (anxiety: r = 0.396; depression: r = 0.486; p < 0.05). Although both anxiety and depression were positively associated with Internet Gaming Disorder, depression emerged as the stronger predictor of gaming disorder tendencies among university students (β = 0.439). These findings suggest that students may engage in gaming as a maladaptive coping strategy to escape emotional distress. Therefore, university counseling services should implement targeted psychological interventions that promote healthy emotion regulation and adaptive coping strategies to reduce the risk of problematic gaming behavior among Generation Z students.